Aluminium-26 from Massive Binary Stars. III. Binary Stars up to Core Collapse and Their Impact on the Early Solar System - Hannah E. Brinkman; Carolyn Doherty; Marco Pignatari; Onno Pols; Maria Lugaro (The Astrophysical Journal, 2023)
Many of the short-lived radioactive nuclei that were present in the early solar system can be produced in massive stars. In the first paper in this series, we focused on the production of ^26 Al in massive binaries. In our second paper, we considered rotating single stars; two more short-lived radioactive nuclei, ^36 Cl and ^41 Ca; and the comparison to the early solar system data. In this work, we update our previous conclusions by further considering the impact of binary interactions. We used the MESA stellar evolution code with an extended nuclear network to compute massive (10–80 M _⊙ ), binary stars at various initial periods and solar metallicity ( Z = 0.014), up to the onset of core collapse. The early solar system abundances of ^26 Al and ^41 Ca can be matched self-consistently by models with initial masses ≥25 M _⊙ , while models with initial primary masses ≥35 M _⊙ can also match ^36 Cl. Almost none of the models provide positive net yields for ^19 F, while for ^22 Ne the net yields are positive from 30 M _⊙ and higher. This leads to an increase by a factor of approximately 4 in the amount of ^22 Ne produced by a stellar population of binary stars, relative to single stars. In addition, besides the impact on the stellar yields, our 10 M _⊙ primary star undergoing Case A mass transfer ends its life as a white dwarf instead of as a core-collapse supernova. This demonstrates that binary interactions can also strongly impact the evolution of stars close to the supernova boundary.